Analisis Penerapan Sistem Informasi Akuntansi pada Siklus Pengeluaran dan Pemasukan Kas: (Studi Kasus pada Firdevs Konveksi) - Ressa Anilah; Gunawan Gunawan (Jurnal Ilmiah Manajemen dan Kewirausahaan, 2025)
Technological advances and the need for efficiency in business management require companies, including the convection sector, to implement an effective accounting information system (AIS). This study aims to analyze the implementation of accounting information systems in the cash inflow and outflow cycle at Firdevs Konveksi. The method used is descriptive research with a qualitative approach, through observation, interviews, and documentation. The study focuses on the recording process, internal control, and the effectiveness of the cash cycle in supporting business operations. The results of the study indicate that the implementation of AIS at Firdevs Konveksi is able to increase the efficiency of cash management, improve the accuracy of financial transaction recording, and strengthen internal control over cash inflow and outflow activities. In addition, the use of accounting information systems helps companies in data-based decision making, increases transparency, and reduces the risk of errors or fraud. This study emphasizes the importance of implementing accounting information systems in supporting business sustainability, especially in the convection sector, by making a significant contribution to more professional, structured, and reliable financial management. Thus, the results of this study are evidence that the implementation of AIS is not only a technical need, but also a strategic factor in increasing the company's competitiveness amidst increasingly competitive business dynamics.